Evaluation of calcium diffusion and pH of the periradicular environment after applying calcium hydroxide or MTA: an in vitro study - Movahedian Attar A; Barekatain B; Farhad A; Niknam O; Alavinejad P (Tehran University of Medical Sciences, 2011)
"nBackground and Aims: It is important to use intracanal medicaments in teeth with necrotic pulp. Calcium hydroxide is the intracanal medicament of choice in such cases. Also, Mineral Trioxide Aggregate (MTA) is a suitable root canal filling material because of its favorable characteristics. MTA can be used in some cases where calcium hydroxide is used. The purpose of this study was to evaluate the Ca++ and OH ˉ diffusion through root dentin using calcium hydroxide paste and two different brands of MTA as root canal filling materials."nMaterials and Methods: In this in vitro study, the root canals of 52 single-rooted teeth were instrumented and shaped. External defects were created on the middle one-third of the root surface. 17% EDTA and 5% NaOCl were used to remove the smear layer. All surfaces except the external defects were sealed and the teeth were placed in normal saline. Ten teeth were selected as the control group. Forty-two remaining teeth were divided into three groups of 14 teeth each (A,B, and C groups). ProRoot MTA was placed in group A. Angelus MTA was placed in group B; and Calcium hydroxide paste was placed in group C. After sealing the coronal access, all specimens were placed in normal saline solution. Ca++ concentration and pH were determined after 24 hours, 48 hours and one week in all groups. The data were analyzed with Repeated Measure ANOVA and Pair T- tests."nResults: Ca++ release and pH in group C was significantly higher than those in groups A and B in all time periods (P<0.001). The difference between groups A and B was not significant (P>0.05)."nConclusion: The results of this study indicate that in necrotic cases with lesion which MTA is indicated (open apex and perforation), calcium hydroxide might be better used as an intracanal dressing before using MTA as a permanent filling material.